2018
DOI: 10.1111/ibi.12643
|View full text |Cite
|
Sign up to set email alerts
|

Measuring ketones in the field: rapid and reliable measures of β‐hydroxybutyrate in birds

Abstract: Ketone bodies such as β‐hydroxybutyrate are important indicators of metabolic condition in birds and are linked to a suite of ecologically relevant factors including migratory decision‐making, hunger level and ectoparasite load. Portable point‐of‐care (POC) devices designed to measure ketones in humans offer a cheap and easy solution to field physiologists in comparison with previous laboratory methods; however, their accuracy for use in birds has received scant attention. Here, we assessed the accuracy of a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The birds were released immediately after sampling. As described by Lindholm et al (2019 ), the device overestimated ketone levels compared to laboratory-derived values; nevertheless, laboratory vs. device values correlated well, indicating that the Optium Xido Neo is accurate enough and to be used in field studies. In nine cases in the parkland area values higher than the device measurement range (0.0–8.0 mM/l), we assumed a value of 8.1 mM/l for calculations.…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…The birds were released immediately after sampling. As described by Lindholm et al (2019 ), the device overestimated ketone levels compared to laboratory-derived values; nevertheless, laboratory vs. device values correlated well, indicating that the Optium Xido Neo is accurate enough and to be used in field studies. In nine cases in the parkland area values higher than the device measurement range (0.0–8.0 mM/l), we assumed a value of 8.1 mM/l for calculations.…”
Section: Methodsmentioning
confidence: 81%
“… Lindholm et al (2019) validated a point-of-care (POC) device for use in birds and found strong agreement of the obtained measurements of the levels of ketone bodies between the device and the widely used standard laboratory methodology. Lindholm et al (2019) studied indoor-raised red junglefowl ( Gallus gallus ), kept under a strict feeding regime.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The time a chicken spends in Phase I largely depends on its hepatic energy reserves (muscle glycogen does not appear to contribute much), with ad libitum-fed broilers depleting their liver glycogen reserves in around 6 h (Warriss et al, 1988), but time courses can vary widely between different chicken strains and feeding strategies. For example, we have seen an approximately 9-fold increase in βHB after 40 h of fasting in 4-week-old Red Junglefowl (Lindholm et al, 2019), while 12-week-old broiler breeders only exhibited a 1.6-fold increase in the same time ( Figure 5).…”
Section: II Iii Fmentioning
confidence: 87%